A ten year (1999-2008) retrospective study of amoebiasis in University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia. - Farhana, F.; Jamaiah, I.; Rohela, M.; Abdul-Aziz, N.M.; Nissapatorn, V. (Malaysian Society of Parasitology and Tropical Medicine, 2009)
This is a ten year (1999-2008) retrospective study of amebiasis in patients admitted to UMMC. A total of 34 cases were analyzed. The most common were amebic liver abscess 22(65%) and the rest were amoebic dysentery 12(35%). Majority of the cases occurred among Malaysians 29(85%), with Chinese 14(41%), followed by the Malays 9(26%) and the Indians 6(18%). Foreigners made up of one Indonesian, one Pakistani and three Myanmarese and constituted 5(15%) of the total cases. Males 24(71%) were more commonly affected. Most of the cases occurred between the age group of 40-49 years, 8(23%) and 60 years and above, 8(23%). Age group of 20-50 years constituted 20(60%) of the cases. The most common clinical presentations were fever with chills and rigors 26(76%), diarrhoea 20 (59%), right hypochondrium pain 17(50%), abdominal pain 17(50%), hepatomegaly 16 (47%) and jaundice 7(20%). All were discharged well after treatment except for one case of death in a 69-year-old Chinese male with amebic liver abscess.